Impact of body composition on fragility fractures in US elderly adults: a population-based study - Xiaohong Huang; Dongxu Zhu; Tianrui Wang; Xiaodong Lian; Yingze Zhang (BMC Geriatrics)
Abstract Objectives The aim of this study was to investigate how variations in body composition impact the likelihood and location of fragility fractures in older adults. Methods Data of US adults aged ≥ 60 years with fragility fracture and body dimension records (n = 13177, representing approximately 334 million US elderly adults) were from NHANES between 1999 and March 2020. We calculated body composition parameters, including the body roundness index (BRI), weight-adjusted waist index (WWI), abdominal visceral fat index (AVI), and arm-to-waist circumference ratio (AC/WC). Linear regression analyzed trends in site-specific fragility fractures, while logistic regression assessed the separate and joint effects of parameters. Results Fragility fractures increased, especially among elderly with central obesity. A rounded body shape (OR4.42 ≤ BRI ≤ 5.60 = 0.6, 95% CI, 0.4–0.9; OR5.61 ≤ BRI ≤ 7.00 = 0.5, 95% CI, 0.3–0.8; ORBRI ≥7.01 = 0.4, 95% CI, 0.2–0.8) and a balanced arm-to-waist size (OR0.32 ≤ AC/WC ≤ 0.33 = 0.6, 95% CI, 0.4–0.9) reduced the risk of hip fractures, and a moderate fat content (OR11.45 cm/√kg ≤WWI≤1.93 cm/√kg = 0.6; 95% CI, 0.4–1.0) lowered the risk of vertebral fractures. Joint analyses found that moderate-built (ORBRI < 4.42, 10.96 cm/√kg ≤WWI≤11.44 cm/√kg = 1.9, 95% CI, 1.3–3.0) elderly faced doubled risk of hip fractures compared to those with severe central obesity (BRI ≥ 7.01, WWI 11.45–11.93 cm/√kg), while mild obesity (OR5.61≤ BRI≤7.00, WWI < 10.96 cm/√kg = 0.1, 95% CI, 0.0–0.6) carried only 10% of this risk. A stocky physique (ORBRI ≥ 7.01, AVI 20.48–23.44 cm²/1000 = 3.6, 95% CI, 1.1–11.1) was a significant risk factor for vertebral fragility fractures, while fit individuals with strong arms (ORBRI < 4.42, AC/WC ≥ 0.34 = 0.7, 95% CI, 0.5–1.0) experienced a lower incidence of vertebral fractures. Conclusions This population-based cohort study identified distinct risk groups for fragility fractures and clearly visualized these high-risk populations, which contributes to preventing fragility fractures and reduce the risk of second fractures.